2023
DOI: 10.1186/s13000-023-01293-0
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based model for predicting the esophagogastric variceal bleeding risk in liver cirrhosis patients

Abstract: Background Liver cirrhosis patients are at risk for esophagogastric variceal bleeding (EGVB). Herein, we aimed to estimate the EGVB risk in patients with liver cirrhosis using an artificial neural network (ANN). Methods We included 999 liver cirrhosis patients hospitalized at the Beijing Ditan Hospital, Capital Medical University in the training cohort and 101 patients from Shuguang Hospital in the validation cohort. The factors independently affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Hemoglobin (HB) is reported as another independent risk factor to evaluate EVH in HBV-induced cirrhosis patients [41]. Spleen width (SW) has also been suggested as an independent predictor of EVH [42]. In our study, we found that there were significant differences in PLT, ALB, HB and SW between patients in the EVs without hemorrhage (EVH−) and EVs with hemorrhage (EVH+) in the single factor analysis.…”
Section: Discussionmentioning
confidence: 51%
“…Hemoglobin (HB) is reported as another independent risk factor to evaluate EVH in HBV-induced cirrhosis patients [41]. Spleen width (SW) has also been suggested as an independent predictor of EVH [42]. In our study, we found that there were significant differences in PLT, ALB, HB and SW between patients in the EVs without hemorrhage (EVH−) and EVs with hemorrhage (EVH+) in the single factor analysis.…”
Section: Discussionmentioning
confidence: 51%
“…This is the first time it has been used in patients with EGVB in cirrhosis. In addition, other models such as clinical-radiomics nomogram16 35 and machine learning-based model15 have been used to predict the risk of EGVB in patients with liver cirrhosis in previous studies. However, the majority of them aimed at the prediction of bleeding risk in patients to prevent the occurrence of EGVB and promote EGVB surveillance strategies.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Therefore, we speculate that this may be the reason for the increasing annual incidence of EGVB. Extensive coverage has been given to customised treatments and interventions aimed at averting the development of additional secondary combinations, 14 diverse perdition models of EVGB 15 16 and evolving treatment techniques. 17 18 These enlighten us that developing a forecasting system for evaluating bleeding risk based on local data, enhancing the technology of intraregional endoscopic and interventional treatment and close follow-up are all significant breakthroughs in managing the escalating incidence rate of EGVB.…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that the sensitivity and specificity could be greater than 70%. Another team tried to manipulate an ANN model, which included both demographic and laboratory parameters, to estimate the 1-year EVB risk[ 19 ]. The model was able to perform the prediction with an AUC of 0.959.…”
Section: Modalities For Evaluating Evb Riskmentioning
confidence: 99%